(untitled) (International Journal of Innovative Technologies in Economy, 2018)
One of the priority directions of the economic reform, currently being carried out in Kazakhstan, is the formation and development of small business. The society is increasingly aware that small business is one of the key conditions for the formation of market mechanisms and is an integral part of the modern market system. Small business is not only a necessary link in the creation of a market system of management, but also the most essential element in the social transformation of society. The state policy in the Republic of Kazakhstan regarding business is aimed at the formation of the middle class, through the development of small entrepreneurship, focused on the creation of new high-tech industries with the greatest added value.